Penggunaan Teknologi Sistem Informasi dan Manajemen sebagai Tehnik untuk Menurunkan Nyeri dan Ansietas pada Pasien Anak - Faruq Ainul Yaqin; Allenidekania Allenidekania; Happy Hayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to synthesize evidence/literature on the use of information system technology in applying active and passive distraction techniques to reduce pain scores in pediatric patients. The research method used in this study is a literature review. The research results based on the search for articles using the PICOT framework in the database Google Scholar were limited to the range of the last ten years, 2010-2020, which obtained five journals. The results showed that active and passive distraction techniques reduced pain scores in pediatric patients. In conclusion, active and passive distraction techniques can be used as non-pharmacological therapy that nurses can do to score pain in pediatric patients. Keywords: Distraction, Pain, Pediatric Patients